PENGARUH SIKAP KONSUMEN DAN MOTIVASI PEMBELIAN TERHADAP KEPERCAYAAN KONSUMEN MENGGUNAKAN APLIKASI TIKET.COM - Yoeliastuti Yoeliastuti; Faridah Faridah (POLITEKNIK LP3I JAKARTA, 2023)
The pandemic era has had an impact on changing patterns of people's lives. Limited space and time lead to increased use of the internet. Through the internet, many conveniences are obtained by the community to fulfill their daily needs, such as buying and selling transactions and ordering products that can be done without face to face using a mobile phone. Application is an important requirement in the online world. The benefits of online applications provide convenience for people anywhere and when they need them. Likewise, the travel business is taking advantage of the pandemic situation by providing online transactions through its application. The daily routine of work causes the boredom and fatigue experienced by today's society. Travel is one way that can be done to eliminate boredom. To meet tourism needs, currently people do not need to queue long to order tickets. To obtain tourist information in the current technological era, the public can use website-based applications such as tiket.com, traveloka.com. pegi-pegi.com and many other ticket booking applications. The rapid development of technology has led to very diverse business competition in any field. Consumer trust in a service provided by the company is the spearhead for the progress of the company. The results of the research conducted by distributing questionnaires revealed that all the results of the instrument assessment were declared valid and reliable. The instrument was declared valid because it obtained the value of t count > t table (valid) and r count > r table, namely 0.312 where r count > 0.60 (Cronbach alpha). The multiple linear regression equation for this study yields Y = 1.997 + 0.365X1 + 1.267 X2 + e Keywords: Consumer Attitudes, Purchase Motivation And Consumer Trust